2016
DOI: 10.1007/s00125-016-4132-z
|View full text |Cite
|
Sign up to set email alerts
|

Exome-chip association analysis reveals an Asian-specific missense variant in PAX4 associated with type 2 diabetes in Chinese individuals

Abstract: Aims/hypothesis Genome-wide association studies (GWASs) have identified many common type 2 diabetes-associated variants, mostly at the intronic or intergenic regions. Recent ad-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
1
24
2
Order By: Relevance
“…Dysregulation of two pancreatic hormones, characterized by insulin insufficiency and hyperglucagonemia, leads to hyperglycemia and contributes to increased diabetes incidence (37). Recently, it has been reported (25,38) that single nucleotide polymorphisms and mutations of PAX4 gene are closely associated with diabetes in numerous ethnic groups. Since PAX4 has opposite roles in the development and function of pancreatic endocrine cells (39), we hypothesized that the dysregulation of the SREBP1c-PAX4 axis might be associated with an imbalance of pancreatic endocrine cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of two pancreatic hormones, characterized by insulin insufficiency and hyperglucagonemia, leads to hyperglycemia and contributes to increased diabetes incidence (37). Recently, it has been reported (25,38) that single nucleotide polymorphisms and mutations of PAX4 gene are closely associated with diabetes in numerous ethnic groups. Since PAX4 has opposite roles in the development and function of pancreatic endocrine cells (39), we hypothesized that the dysregulation of the SREBP1c-PAX4 axis might be associated with an imbalance of pancreatic endocrine cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the overexpression of PAX4 protects b-cells from apoptosis induced by streptozotocin (STZ) (24). Recently, it has been reported that mutations of the PAX4 gene are associated with type 1 and 2 diabetes as well as ketosis-prone diabetes in various ethnic groups (25). Although the correlation between PAX4 dysfunction and diabetes has been demonstrated, the regulatory mechanism of PAX4 expression remains elusive.…”
mentioning
confidence: 99%
“…This study consisted of an exome-chip association study evaluating the genetic determinants of the circulating PEDF level in 5,385 Chinese subjects with T2D. The discovery stage involved 2,936 subjects who had been examined in our previous exome-chip association studies (26)(27)(28), followed by a replication study in 2,449 independent subjects with T2D who had not been genotyped with the exome chip. The cross-sectional associations of circulating PEDF levels and the PEDF-associated single nucleotide polymorphisms (SNPs) with diabetes complications were then examined.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects were genotyped using the custom Asian exomechip (13,14) with an add-on content of 58,317 single nucleotide polymorphisms (SNPs), including a custom panel of over 30,000 missense or nonsense coding variants on top of the standard content of the Infinium HumanExome Bead-Chip (HumanExome-12v1_A; Illumina, San Diego, CA). Genotyping of the exome array was performed using the Illumina iScan system platform at the Centre for Genomic Sciences of The University of Hong Kong.…”
Section: Genotyping and Data Quality Controlmentioning
confidence: 99%
“…This study sought to identify the genetic determinants of circulating FGF21 levels. We conducted an exome-chip association analysis on circulating FGF21 levels using a specially designed Illumina HumanExome BeadChip (Asian exome-chip) in a Chinese population (13,14). In consideration of the possible difference in circulating FGF21 levels between individuals from the patient groups and those from the general population, possibly due to the intrinsic metabolic stress under disease conditions and the treatment effects on FGF21 expression, we first conducted the association analysis in a community-based and two clinic-based cohorts separately, followed by a combined analysis involving a total of 5,169 individuals.…”
mentioning
confidence: 99%